The 2022 extreme drought in the Yangtze River Basin: Characteristics, causes and response strategies. Issue 2 (5th December 2022) - Ma, Miaomiao; Qu, Yanping; Lyu, Juan; Zhang, Xuejun; Su, Zhicheng; Gao, Hui; Yang, Xiaojing; Chen, Xixi; Jiang, Tianliang; Zhang, Jiexiang; Shen, Mengyan; Wang, Zhe
Abstract: An extreme drought occurred in the Yangtze River Basin in 2022, inflicting huge impacts nationwide. To provide a reference for drought prevention and mitigation, this paper presents a comprehensive analysis of the drought in the Yangtze River Basin in terms of its characteristics, causes, impacts, and response strategies. It concludes that this extreme drought stood out by its long duration, wide impact range, and severe intensity, as a combined result of abnormal high‐temperature weather and massive social water consumption. Serious impacts are observed in various fields of the economy, including agricultural irrigation, urban and rural water supply, power generation, and navigation. Finally, drought mitigation measures and effects are examined, and future drought response and mitigation strategies are proposed.